Answer:
-3 is the answer for the question
Answer:
0.166
Step-by-step explanation:
The term that best describes a proof in which you assume the opposite of what you want to prove is proof of contradiction. Contradiction means opposite.
Your answer is: C) Proof of Contradiction
Have an amazing day!
![6 - 2x = 6x - 10x + 4](https://tex.z-dn.net/?f=6%20-%202x%20%3D%206x%20-%2010x%20%2B%204)
![6 - 2x = - 4x + 4](https://tex.z-dn.net/?f=6%20-%202x%20%3D%20%20-%204x%20%2B%204)
![6 = - 4x + 4 + 2x](https://tex.z-dn.net/?f=6%20%3D%20%20-%204x%20%2B%204%20%2B%202x)
![6 = - 2x + 4](https://tex.z-dn.net/?f=6%20%3D%20%20-%202x%20%2B%204)
![- 2x + 4 = 6](https://tex.z-dn.net/?f=%20-%202x%20%2B%204%20%3D%206)
![- 2x = 6 - 4](https://tex.z-dn.net/?f=%20-%202x%20%3D%206%20-%204)
![- 2x = 2](https://tex.z-dn.net/?f=%20-%202x%20%3D%202)
![x = \frac{ \: \: \: 2}{ - 2}](https://tex.z-dn.net/?f=x%20%3D%20%20%5Cfrac%7B%20%5C%3A%20%20%5C%3A%20%20%5C%3A%202%7D%7B%20-%202%7D%20)
![x = - 1](https://tex.z-dn.net/?f=x%20%3D%20%20-%201)
Therefore , the value of x = -1
I cant read it ..........................................................